The epidemic of multidrug resistant tuberculosis in China in historical and phylogenetic perspectives. Issue 4 (April 2020) - Zhou, Yang; Anthony, Richard; Wang, Shengfen; Ou, Xichao; Liu, Dongxin; Zhao, Yanlin; Soolingen, Dick van
Abstract: Objectives: For the past decade, the epidemic of multidrug resistance tuberculosis (MDR-TB) stays high in China. We investigated the possible driving forces behind the epidemics from phylogenetic and historical perspectives. Methods: 420 representative strains were selected from the first national drug resistance survey based on their genotypes, drug susceptibility patterns and geographic information. We reconstructed the phylogeny by whole genome sequencing and compared it to the global phylogeny including MDR outbreaks reported in other settings. We estimated the historical trajectory of population dynamics by Bayesian Skygrid plot for all strains and MDR-TB alone. Integrating geographic information and mutations in drug resistance related genes, we investigated the spatial scale of transmission, recent selection of drug resistant mutant, and mechanism for fitness restoration. Results: Three new subgroups within Beijing clade are described for the first time, but none of the MDR-TB outbreak strains reported in other high MDR-TB burden settings is identified. The overall epidemics experienced two successive phases of expansion at different rates between 1660s and 1950s, followed by a sharp decline till today. Four fifths of the clustered MDR-TB strains suggest transmission of DR strains and nearly half suggest recent selection of (additional) mutations in rpoB . Among all identified transmission events, about one fifth occurred between far distant locations. Possible intergenic and intragenic compensatory mutations both presented in our dataset at comparable frequencies. Conclusions: MDR-TB epidemic in China is not yet driven by the spread of a few highly successful clonal expansions but by repeated emergence of smaller and currently less successful clusters. However, internal migration and undertreatment could escalate MDR-TB epidemic. To prevent generating of drug resistance and restoration of fitness as well as to stop transmission of MDR-TB at early stage, national TB control program needs to strengthen management of floating populations and promote universal drug susceptibility testing in China.